Bumi sebagai Kampung Sejati Manusia: Telaah QS. Nuh [71]: 17–20 dalam Pespektif Tafsir Sains - Tri Ridho Andani; Rizky Ma'ruf Habibie; Cecep Zakarias El Bilad (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2026)
This study examines the relationship between humans and the earth in Surah Nuh [71]: 17–20 through the perspective of scientific exegesis. The focus of this study is to understand the connection between humans and the earth as the source of creation, a place of life, and a place of return after death. The novelty of this study lies in the integration of Qur’anic exegesis with modern science regarding the elements that compose the human body, which originate from the earth. This study employs a literature review (library research) using a descriptive-analytical approach. The results indicate that humans have a close relationship with the earth, both theologically and scientifically. The human body is composed of elements such as oxygen, carbon, minerals, and water that originate from the earth. Furthermore, the concept of the earth as a “spread-out expanse” in the Qur’an does not contradict the scientific fact that the earth is spherical. This study concludes that the earth is humanity’s “true homeland,” and thus humans bear the responsibility to preserve its sustainability.